Large-scale synthesis of Sb2S3 spikes by hydrothermal reaction - Chalermchai Pilapong (2018)
Spikes of Sb2S3 (antimony sulfide) were synthesized by hydrothermal reaction at 100-200 °C for 6-48 h. By using X-ray diffraction (XRD), selected area electron diffraction (SAED), field emission scanning electron microscopy (FE-SEM), transmission electron microscopy (TEM), high resolution TEM (HRTEM) and UV-vis absorption spectroscopy, the products were specified as orthorhombic Sb2S3 in the shape of spikes, with their growths in the [001] direction and Eg of 5.40 eV. A diffraction pattern was also simulated, and was in good accordance with the SAED pattern obtained from the experiment. ©2010 IEEE.